An augmented-reality system prototype for guiding transcranial Doppler ultrasound examination - Xiao, Yiming; Drouin, Simon; Gerard, Ian J.; Fonov, Vladimir; Aubert-Broche, Bérengère; Ma, Yuhan; Kersten-Oertel, Marta; Tampieri, Donatella; Collins, D. Louis (Multimedia tools and applications, 2018)
Ultrasound (US) is a popular medical imaging technique in the clinic due to its low cost, high portability, and real-time diagnostic value. A special type of ultrasound technique, transcranial Doppler (TCD) ultrasound can be used to measure blood flows in cerebral blood vessels through acoustic bone windows of the intact human skull. Although TCD ultrasound is commonly used to diagnose and monitor a range of neurovascular conditions, such as stroke, interpretation of the image content in the TCD scans and quick localization of the targeted blood vessels with it can be difficult due to inherent challenges of its unique image contrasts, relatively low image quality, and 2D nature of the technique in relation to the 3D brain anatomy that is invisible to the clinician. These drawbacks may hinder the efficiency and even accuracy of the TCS examinations, especially for novel users. To render the procedure more efficient and intuitive, we developed a prototype of augmented-reality system to guide the procedure by fusing a population-averaged probabilistic blood vessel atlas with camera footages of the patient. The system prototype was demonstrated with healthy subjects, and is expected to facility the clinical TCD examination, as well as to help in the educational context for new clinicians and clinical technicians.